Clinical and Parasitological Profiles of Gestational, Placental and Congenital Malaria in Northwestern Colombia - Jaiberth Antonio Cardona-Arias; Luis Felipe Higuita-Gutiérrez; Jaime Carmona-Fonseca (Tropical Medicine and Infectious Disease, 2023)
This study compared the clinical–parasitological profiles of gestational (GM), placental (PM), and congenital (CM) malaria in northwestern Colombia. A cross-sectional study with 829 pregnant women, 549 placentas, and 547 newborns was conducted. The frequency of GM was 35.8%, PM 20.9%, and CM 8.5%. P. vivax predominated in GM; in PM, the proportion of P. vivax and P. falciparum was similar; in CM, P. falciparum predominated. The main clinical findings were headache (49%), anemia (32%), fever (24%), and musculoskeletal pain (13%). The clinical manifestations were statistically higher in P. vivax infections. In submicroscopic GM (positive with qPCR and negative with thick blood smear), the frequency of anemia, sore throat, and a headache was statistically higher compared with pregnant women without malaria. GM, PM, and CM reduce birth weight and head circumference. In Colombia, this is the first research on the clinical characteristics of GM, PM, and CM; contrary to evidence from other countries, P. vivax and submicroscopic infections are associated with clinical outcomes.